Didática para a Educação Infantil: implicações do materialismo histórico dialético e da Teoria Histórico-Cultural - Castro, Rosane Michelli de [UNESP]; Lima, Elieuza Aparecida de [UNESP] (My University, 2012)
In this article, we discuss the contributions of Didactics for intentional pedagogical action of teachers devoted to children education. In this sense, we initially say to be essential the reflections which aim to search for foundations focused on the mobilization of future teachers for the action-reflection-action about the educational phenomena, aiming at the unveiling, with rigor and objectivity, of its multiple determinations within the capitalist relations . We believe that such unveiling is only possible in the light of a world view, a method and a praxis constituted in unison with historical materialism and its dialectic. Afterwards, we reflect on some of the principles of the Historical-Cultural Theory to understand of the active and mediator role teachers have in the process of humanization of young children and contributions of dialectical materialism to this reflection. Finally are detailed some aspects of a Didactics focused on training teachers for Children and early elementary school years’ education, which have guided our actions as teachers of the Pedagogy Course and reiterated by teachers’ narratives about their experience both in life and teaching, in search of new systematization modes, targeting an educational praxis due to the redefinition (theorization) and on the teaching practice by its very subjects.

Neste artigo, discutimos acerca de contribuições da Didática para uma atuação pedagógica intencional de professores dedicados à educação infantil. Nesse sentido, inicialmente, afirmamos serem essenciais as reflexões que visam à busca de fundamentos focados na mobilização dos futuros docentes para a ação-reflexão-ação acerca dos fenômenos educativos, objetivando o desvelamento, com rigor e objetividade, de suas múltiplas determinações no âmbito das relações capitalistas. Acreditamos que esse desvelamento seja possível apenas à luz de uma concepção de mundo, de um método e de uma práxis que se constituem em unidade no materialismo histórico e na sua dialética. Na sequência, refletimos sobre alguns dos princípios da Teoria Histórico-Cultural para entendimento do lugar ativo e mediador do professor no processo de humanização das crianças pequenas e contribuições do materialismo dialético para esta reflexão. Finalmente, são explicitados aspectos de uma Didática voltada para a formação de professores para a educação Infantil e dos anos iniciais do ensino fundamental, os quais têm norteado nossas condutas como professoras do Curso de Pedagogia e reafirmadas nas narrativas de professores sobre suas vivências e experiências docentes, em busca de novas sistematizações, mirando uma prá- xis pedagógica decorrente da ressignificação (teorização) da e sobre prática pedagógica, pelos próprios sujeitos.
Didactics for children education: implications of dialectical and historical materialism and historical-cultural theory
Keywords: Educação; Didática; educação infantil